CBX4 promotes the proliferation and metastasis via regulating BMI‐1 in lung cancer. Issue 1 (13th November 2019) - Hu, Changpeng; Zhang, Qian; Tang, Qin; Zhou, Huyue; Liu, Wuyi; Huang, Jingbin; Liu, Yali; Wang, Qin; Zhang, Jing; Zhou, Min; Sheng, Fangfang; Lai, Wenjing; et al.
Abstract: Proliferation and metastasis are significantly malignant characteristics of human lung cancer, but the underlying molecular mechanisms are poorly understood. Chromobox 4 (CBX4), a member of the Polycomb group (PcG) family of epigenetic regulatory factors, enhances cellular proliferation and promotes cancer cell migration. However, the effect of CBX4 in the progression of lung cancer is not fully understood. We found that CBX4 is highly expressed in lung tumours compared with adjacent normal tissues. Overexpression of CBX4 significantly promotes cell proliferation and migration in human lung cancer cell lines. The knockdown of CBX4 obviously suppresses the cell growth and migration of human lung cancer cells in vitro. Also, the proliferation and metastasis in vivo are blocked by CBX4 knockdown. Furthermore, CBX4 knockdown effectively arrests cell cycle at the G0/G1 phase through suppressing the expression of CDK2 and Cyclin E and decreases the formation of filopodia through suppressing MMP2, MMP9 and CXCR4. Additionally, CBX4 promotes proliferation and metastasis via regulating the expression of BMI‐1 which is a significant regulator of proliferation and migration in lung cancer cells. Taken together, these data suggest that CBX4 is not only a novel prognostic marker but also may be a potential therapeutic target in lung cancer.